Mechanisms of torsades de pointes: an update - Tsuji, Yukiomi; Yamazaki, Masatoshi; Shimojo, Masafumi; Yanagisawa, Satoshi; Inden, Yasuya; Murohara, Toyoaki (Frontiers in Cardiovascular Medicine, 2024)
Torsades de Pointes (TdP) refers to a polymorphic ventricular tachycardia (VT) with undulating QRS axis that occurs in long QT syndrome (LQTS), although the term has been used to describe polymorphic ventricular tachyarrhythmias in which QT intervals are not prolonged, such as short-coupled variant of TdP currently known as short-coupled ventricular fibrillation (VF) and Brugada syndrome. Extensive works on LQTS-related TdP over more than 50 years since it was first recognized by Dessertennes who coined the French term meaning "twisting of the points", have led to current understanding of the electrophysiological mechanism that TdP is initiated by triggered activity due to early afterdepolarization (EAD) and maintained by reentry within a substrate of inhomogeneous repolarization. While a recently emerging notion that steep voltage gradients rather than EADs are crucial to generate premature ventricular contractions provides additions to the initiation mode, the research to elucidate the maintenance mechanism hasn't made much progress. The reentrant activity that produces the specific form of VT is not well characterized. We have conducted optical mapping in a rabbit model of electrical storm by electrical remodeling (QT prolongation) due to chronic complete atrioventricular block (CAVB) and demonstrated that a tissue-island with prolonged refractoriness due to enhanced late Na + current (INa-L) contributes to the generation of drifting rotors in a unique manner, which may explain the ECG characteristic of TdP. Moreover, we have proposed that the neural Na + channel NaV1.8-mediated INa-L may be a new player to form the substrate for TdP.Here we discuss TdP mechanisms by comparing the findings in electrical storm rabbits with recently published studies by others in simulation models and human and animal models of LQTS.